Pengaruh Laboratorium Virtual Berbasis Problem Solving Terhadap Kemampuan Berpikir Kritis - Ewi Mellysa Barus; Terry Noviar Panggabean (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
The availability of facilities and infrastructure in learning Cell and molecular biology courses is needed to support the achievement of learning objectives. Based on the results of observations in the Imelda University, Pharmacy Department, the lack of implementation due to the lack of facilities and infrastructure that support the practicum causes a lack of improvement in students' critical thinking skills. The ability to think critically is the main factor affecting student understanding. In this case, the media that can support this is a problem solving-based virtual laboratory to encourage students' critical thinking skills. This study aims to identify the effect of a problem solving-based virtual biology laboratory on the critical thinking skills of students in the Pharmacy Undergraduate Study Program at Imelda University, Medan. The research design was one group pre-test posttest. Data collection was carried out starting in January 2020, followed by data processing and analysis. The sample in this study were all students of the first semester Pharmacy Department at Imelda University, totaling 63 people. The sampling technique in this study is total sampling. The statistical analysis used was one sample T-test. Based on the results of the discussion based on the problems and research objectives, it can be concluded that there is a positive and significant effect with p 0.00 <0.05 in the use of problem solving-based virtual laboratories on students' critical thinking skills in the cell and molecular biology courses at the Imelda University Pharmacy Department. With the virtual laboratory, students learn the principles of science in a fast, effective and fun way through virtual laboratory interactions and navigation.